امام غزالی: شخصیت و افکار : Imam Ghazali: Biography and Thoughts - Younus (Translator), Muhammad; Moosa (Author), Ebrahim (FIKR-O NAZAR فکر ونظر, 2023)
This research article intricately examines the evolution of Muḥammad b. Muḥammad al-Ghazālī’s jurisprudential thought within the expansive framework of Islamic intellectual history. Al-Ghazālī’s intellectual journey unfolds through five discernible phases, initiating with steadfast adherence to the Shāfi‘ī school and progressing towards a nuanced integration of ethical perspectives, profoundly influenced by mysticism. Beyond al-Ghazālī’s recognized juristic prowess, particular attention is devoted to his Sufi phase, emphasizing the ethical dimensions inherent in religious teachings. A focal point is al-Ghazālī’s magnum opus, Iḥyā’ ‘Ulūm al-Dīn, a work that advocates for a profound reevaluation of disciplines such as law, theology, and ethics, emphasizing the centrality of self-transformation and piety within the realm of jurisprudence. Pioneering the discourse on the purposes (maqāṣid) of the sharī‘ah, al-Ghazālī aligns these purposes with the utilitarian principle of maṣlaḥah, grounding his ethical framework in values revealed by the Islamic tradition. Despite his endorsement of purposive reasoning, al-Ghazālī exhibits judicious caution, emphasizing alignment with established legal practices. This research article sheds light on al-Ghazālī’s enduring legacy as a jurist, scholar, and mystic, unveiling his profound impact on the Shāfi‘ī school and his groundbreaking discourse on the ethical dimensions inherent in Islamic jurisprudence. Al-Ghazālī’s pervasive influence reverberates within Islamic intellectual spheres and extends to broader academic discourse.